Echocardiographic Doppler estimation of pulmonary artery pressure in critically ill patients with severe hypoxemia - Bouhemad, Bélaïd [UNESP]; Ferrari, Fabio [UNESP]; Leleu, Kris; Arbelot, Charlotte; Lu, Qin; Rouby, Jean-Jacques (Wolters Kluwer, 2008)
BACKGROUND: In spontaneously breathing cardiac patients, pulmonary artery pressure (PAP) can be accurately estimated from the transthoracic Doppler study of pulmonary artery and tricuspid regurgitation blood flows. In critically ill patients on mechanical ventilation for acute lung injury, the interposition of gas between the probe and the heart renders the transthoracic approach problematic. This study was aimed at determining whether the transesophageal approach could offer an alternative. METHODS: Fifty-one consecutive sedated and ventilated patients with severe hypoxemia (arterial oxygen tension/fraction of inspired oxygen < 300) were prospectively studied. Mean PAP measured from the pulmonary artery catheter was compared with several indices characterizing pulmonary artery blood flow assessed using transesophageal echocardiography: preejection time, acceleration time, ejection duration, preejection time on ejection duration ratio, and acceleration time on ejection duration ratio. In a subgroup of 20 patients, systolic PAP measured from the pulmonary artery catheter immediately before withdrawal was compared with Doppler study of regurgitation tricuspid flow performed immediately after pulmonary artery catheter withdrawal using either the transthoracic or the transesophageal approach. RESULTS: Weak and clinically irrelevant correlations were found between mean PAP and indices of pulmonary artery flow. A statistically significant and clinically relevant correlation was found between systolic PAP and regurgitation tricuspid flow. In 3 patients (14%), pulmonary artery pressure could not be assessed echocardiographically. CONCLUSIONS: In hypoxemic patients on mechanical ventilation, mean PAP cannot be reliably estimated from indices characterizing pulmonary artery blood flow. Systolic PAP can be estimated from regurgitation tricuspid flow using either transthoracic or transesophageal approach. © 2008 American Society of Anesthesiologists, Inc.
Keywords: atracurium; fentanyl; midazolam; nitric oxide; adult; arterial oxygen tension; artificial ventilation; controlled study; critically ill patient; disease severity; Doppler echocardiography; female; heart ventricle ejection time; human; hypoxemia; lung artery pressure; lung blood flow; major clinical study; male; priority journal; pulmonary artery catheter; sedation; statistical significance; systolic blood pressure; transesophageal echocardiography; tricuspid valve regurgitation; Adult; Aged; Anoxia; Critical Illness; Echocardiography, Doppler; Female; Humans; Male; Middle Aged; Prospective Studies; Pulmonary Artery; Pulmonary Wedge Pressure